Impact of Left Ventricular Ejection Fraction on Clinical Outcomes Over Five Years After Infarct-Related Coronary Artery Recanalization (from the Occluded Artery Trial [OAT]) - Kruk, Mariusz (2010)
In the Occluded Artery Trial (OAT), percutaneous coronary intervention (PCI) of an infarct-related artery on days 3 to 28 after acute myocardial infarction was of no benefit compared to medical therapy alone. The present analysis was conducted to determine whether PCI might provide benefit to the subgroup of higher risk patients with a depressed ejection fraction (EF). Of 2,185 analyzed patients (age 58.6 ± 11.0 years) with infarct-related artery occlusion on days 3 to 28 after acute myocardial infarction in the Occluded Artery Trial, 1,094 were assigned to PCI and 1,091 to medical therapy. The primary end point was a composite of death, reinfarction, and New York Heart Association class IV heart failure. The outcomes were analyzed by EF (first tertile, EF ≤44%, vs second and third tertiles combined, EF >44%). Interaction of the treatment effect with EF on the study outcomes were examined using the Cox survival model. The five-year rates of the primary end point (death, reinfarction, or New York Heart Association class IV heart failure) were not different in either subgroup (PCI vs medical therapy, hazard ratio 1.25, 99% confidence interval 0.83 to 1.88, for EF ≤44%; hazard ratio 0.98, 99% confidence interval 0.64 to 1.50, for EF >44%). However, in patients with an EF >44%, PCI reduced the rate of subsequent revascularization (p = 0.004, interaction p = 0.05). In conclusion, optimal medical therapy remains the overall treatment of choice for stable patients with a persistent total occlusion of the infarct-related artery after acute myocardial infarction, irrespective of the baseline EF. In patients with normal or moderately impaired left ventricular contractility, PCI reduced the need for subsequent revascularization but did not otherwise improve outcomes.